TRIM21 Dysfunction Enhances Aberrant B-Cell Differentiation in Autoimmune Pathogenesis - Kunishita, Yosuke; Yoshimi, Ryusuke; Kamiyama, Reikou; Kishimoto, Daiga; Yoshida, Koji; Hashimoto, Eijin; Komiya, Takaaki; Sakurai, Natsuki; Sugiyama, Yumiko; Kirino, Yohei; Ozato, Keiko; Nakajima, Hideaki (Frontiers in Immunology, 2020)
TRIM21 is one of the autoantigens that reacts with an anti-SS-A antibody (Ab) present in patients with systemic lupus erythematosus (SLE) and Sjögren's syndrome. TRIM21 is thought to play a role in B-cell proliferation and apoptosis, among other activities. Here we examined a pathological role of TRIM21 in SLE. Trim21-deficient MRL/lpr mice were generated by backcrossing Trim21-deficient C57BL/6 mice to MRL/lpr mice. The levels of serum anti-dsDNA Ab and urine protein at 28 weeks of age were significantly higher in Trim21-deficient MRL/lpr mice as compared to wild-type MRL/lpr mice (p = 0.029 and 0.003, respectively). Resting B cells from Trim21-deficient mice showed significantly higher abilities to differentiate into plasmablasts and to produce Ab as compared with control mice. Due to the reduction of TRIM21-mediated ubiquitylation, IRF5 protein expression was increased in Trim21-deficient MRL/lpr mice (p = 0.021), which correlated with increased plasmablast generation and immunoglobulin production. B cells from SLE patients with anti-TRIM21 Ab seropositivity also showed a significantly higher ability to differentiate into plasmablasts as compared with those without anti-TRIM21 Ab or healthy controls. These results suggest that TRIM21 dysfunction contributes to SLE pathogenesis by promoting B-cell differentiation, for which anti-TRIM21 Ab may be partly responsible.